A study on phenotypic traits of Candida species isolated from blood stream infections and their in vitro susceptibility to fluconazole - Amit Kumar; P.C. Sharma; Ajay Kumar; Vishwanand Negi (Al Ameen Medical College, 2014)
Background & objectives: Fungal infections are increasing very rapidly. Candida is a major pathogen involved and constitutes a part of normal microflora of humans. This organism is a leading agent associated with blood stream infections. The present study involves phenotypic characterization of Candida isolates. The isolates were obtained from National Culture Collection of Pathogenic Fungi at Post Graduate Institute of Medical Education and Research, Chandigarh, India. Keeping in view the rising trend of resistance by the Candida species to various antifungal agents their susceptibility has also been studied. Methods: All the isolates were identified upto species level by studying their phenotypic and biochemical characteristics. Phenotypic traits of Candida isolates studied included: formation of pseudohyphae, chlamydospore production, germ tube production, fermentation and assimilation of various sugars by the different species of Candida. All the isolates were tested for their susceptibility to fluconazole by disc diffusion and micro broth dilution methods. Results: The isolates could be clearly differentiated from each other by their phenotypic traits studied. A total of 51 out of 67 isolates examined (76.11%) were sensitive to fluconazole, 6 were sensitive dose dependent and 10 exhibited resistance to this drug. Among the resistant species C. albicans figured on the top followed by C. tropicalis, C. guillermondii and C. glabrata. However, resistance to fluconazole was not observed by C.parapsilosis isolates. Conclusions: The present study would help in the diagnosis of Candida species from clinical samples and give clue about the susceptibility of different species of Candida to fluconazole which might helpin the management of candidal infections.